2009
DOI: 10.1542/peds.2008-1606
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment and Management of Toddlers With Suspected Autism Spectrum Disorder: Insights From Studies of High-Risk Infants

Abstract: With increased public awareness of the early signs and recent American Academy of Pediatrics recommendations that all 18- and 24-month-olds be screened for autism spectrum disorders, there is an increasing need for diagnostic assessment of very young children. However, unique challenges exist in applying current diagnostic guidelines for autism spectrum disorders to children under the age of 2 years. In this article, we address challenges related to early detection, diagnosis, and treatment of autism spectrum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
263
0
16

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 356 publications
(291 citation statements)
references
References 99 publications
7
263
0
16
Order By: Relevance
“…[35][36][37][38] The red flags identified should be followed by immediate referral for infant intervention rather than adopting a "wait-andsee" attitude because early specialized intervention is considered best practice for ASD 39,40 and may represent the best hope for reducing symptoms and overall disability in high-risk infants who are developing ASD. 41 …”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38] The red flags identified should be followed by immediate referral for infant intervention rather than adopting a "wait-andsee" attitude because early specialized intervention is considered best practice for ASD 39,40 and may represent the best hope for reducing symptoms and overall disability in high-risk infants who are developing ASD. 41 …”
Section: Discussionmentioning
confidence: 99%
“…7 However, late identification of ASD is a wellknown problem, even in developed countries. 8 A recent review article including data from 42 studies (from 1990 to 2012) showed that the mean age of ASD diagnosis ranged from 38 to 120 months.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, estudos prospectivos realizados com irmãos de indivíduos com TEA, cujo risco estimado de também apresentarem o transtorno é de 5 a 10% (Rice et al, 2007), têm identificado diversos comportamentos manifestados entre 12 e 18 meses, que distinguem os bebês com TEA de outros com desenvolvimento típico (Zwaigenbaum et al, 2009).…”
Section: Discussionunclassified